detectability of the colour pattern in the aposematic firebug, Pyrrhocoris apterus: an image‐based experiment with human ‘predators’ - BOHLIN, TITTI; GAMBERALE‐STILLE, GABRIELLA; MERILAITA, SAMI; EXNEROVÁ, ALICE; ŠTYS, PAVEL; TULLBERG, BIRGITTA S (Biological journal of the Linnean Society, 2012)
Crypsis and aposematism are often regarded as two opposite protective strategies. However, there is large variation in prey appearance within both strategies. In this article, we investigated the conspicuousness of the aposematic red‐and‐black firebug, Pyrrhocoris apterus, by presenting images of natural and digitally manipulated phenotypes in their natural habitat on a computer screen to human ‘predators’, and comparing the detection times. We asked whether the natural colour pattern can be made more or less conspicuous by rearranging the spatial distribution of colour elements. Hence, we created a phenotype in which the black colour elements were moved to the body outline to test for a possible disruptive effect. In the ‘black’ and ‘red’ manipulations, we removed one of the two colours, creating two uniform colour variants. We found that some of our manipulations increased, but none reduced, the detection time significantly; this indicates that the naturally coloured firebug is highly conspicuous. The detection time varied among backgrounds and there was a significant relationship between detection time and chromatic similarity between the bug and the background for the natural and black phenotypes. Although background colour composition has an important effect on the signal, we argue that the coloration of P. apterus has evolved for high conspicuousness. © 2012 The Linnean Society of London, Biological Journal of the Linnean Society, 2012, 105, 806–816.